2. KNOWLEDGE, PRACTICE, AND SOME FACTORS AFFECTING THE SAFETY OF INJECTIONS BY NURSES AT THU DUC CITY HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to describe the demographic characteristics of nurses and assess the rates of knowledge and practices regarding safe injection, as well as identify factors influencing these aspects among nurses at Thu Duc City Hospital in 2024.Research objects and methods: A cross-sectional descriptive study was conducted involving 218 nurses working in clinical departments who provide direct patient care and perform injection techniques at Thu Duc City Hospital in 2024Results: The average age of the participating nurses was 31.64 years, with a female-to-maleratio of 5:1. Nurses with undergraduate or higher education constituted 59.2%, and those with work experience of 5 years or more made up 76.1%. The proportions of nurses with adequate knowledge and practices regarding safe injection were 51% and 58.3%, respectively. The mean knowledge score was 22.58 ± 2.28, and the mean practice score was 18.95 ± 2.88. Age and years of experience were statistically significant factors related to knowledge and practices of safe injection among nurses (p
Keywords: Knowledge; practices; safe injection; nursing